Four concepts for resilience and the implications for the future of resilience engineering. (September 2015) - Woods, David D.
Abstract: The concept of system resilience is important and popular—in fact, hyper-popular over the last few years. Clarifying the technical meanings and foundations of the concept of resilience would appear to be necessary. Proposals for defining resilience are flourishing as well. This paper organizes the different technical approaches to the question of what is resilience and how to engineer it in complex adaptive systems. This paper groups the different uses of the label 'resilience' around four basic concepts: (1) resilience as rebound from trauma and return to equilibrium; (2) resilience as a synonym for robustness; (3) resilience as the opposite of brittleness, i.e., as graceful extensibility when surprise challenges boundaries; (4) resilience as network architectures that can sustain the ability to adapt to future surprises as conditions evolve. Highlights: There continues to be a wide diversity of definitions of the label resilience. Research progress points to 4 basic concepts underneath diverse uses of. Each of the four core concepts defines different research agendas. The 4 concepts provide guides on how to engineer resilience for safety.